2015
DOI: 10.1039/c5cc03972j
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent probe for hypochlorite based on the modulation of the unique rotation of the N–N single bond in acetohydrazide

Abstract: Herein, a novel signaling mechanism for constructing fluorescent probes was demonstrated for the first time based on modulation of the unique rotation of the N-N single bond in the acetohydrazide group. According to the new signaling mechanism, a fluorescent probe for hypochlorite was then judiciously developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Concerning potential sensing applications this is attractive, since “blacklight” can be used for the efficient excitation of the fluorophore producing a bright, blue fluorescence. A coumarin‐tagged azolium salt as the precursor to the respective NHC–metal complexes is easily available from the amide‐forming reaction of 7‐NEt 2 ‐coumarin‐3‐carboxylic acid chloride 1 and the aminoethyl‐substituted azolium salt 2 in 78 % yield (Scheme ), followed by an ion‐exchange reaction converting the BF 4 – into the chloride salt 3· HCl.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning potential sensing applications this is attractive, since “blacklight” can be used for the efficient excitation of the fluorophore producing a bright, blue fluorescence. A coumarin‐tagged azolium salt as the precursor to the respective NHC–metal complexes is easily available from the amide‐forming reaction of 7‐NEt 2 ‐coumarin‐3‐carboxylic acid chloride 1 and the aminoethyl‐substituted azolium salt 2 in 78 % yield (Scheme ), followed by an ion‐exchange reaction converting the BF 4 – into the chloride salt 3· HCl.…”
Section: Resultsmentioning
confidence: 99%
“…The Zhang group in 2015 reported that the rotation of the C-N single bond in the acetohydrazide moiety lead to the quenching of the fluorescence of af luorophore as shown below (Scheme 109). [118] Based on this straightforwardc oncept, they designeda nd synthesized the probe for selectived etec-tion of hypochlorite. The probe exhibiteda lmost non-fluorescent due to the rotation of the N-N-single bond in the acetohydrazide moiety;h owever, upon reaction with HOCl, the C-N single bond in the probe was cleaved and led to the recovery of the fluorescence.…”
Section: Scheme93mentioning
confidence: 99%
“…The Zhang group in 2015 reported that the rotation of the C–N single bond in the acetohydrazide moiety lead to the quenching of the fluorescence of a fluorophore as shown below (Scheme ) . Based on this straightforward concept, they designed and synthesized the probe for selective detection of hypochlorite.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorometric analysis with OCl À -selective molecular sensors is one promising method for this purpose since this facilitates simple quantication or imaging of OCl À with a common uorescence spectrometer or microscope apparatus. 9 A number of uorescent OCl À sensors have been reported; [10][11][12][13][14][15][16][17] however, many of them require tedious multi-step procedures for the synthesis of sensors or a solution containing a large amount of organic solvents for sensing due to the low solubility of the sensors in water. Among the previously reported OCl À sensors, a "dihydroperimidine"-based sensor designed by Goswami et al 18 has the simplest structure, which can be prepared by a facile condensation.…”
Section: Introductionmentioning
confidence: 99%